2019
DOI: 10.21037/sci.2019.10.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet-rich plasma from diabetic donors shows increased platelet vascular endothelial growth factor release

Abstract: Background: Platelet-rich plasma (PRP) contains pro-angiogenic growth factors including vascular endothelial growth factor (VEGF). Angiogenesis is a necessary component of wound healing in instances of diabetic foot ulcers (DFU). PRP composition varies depending on methods and donor health status. Our group has developed an improved PRP protocol for diabetes treatment. The aims of this study were to examine the levels of the pro-angiogenic factor VEGF in these patient populations with and without diabetes.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Marx reported that double centrifugation of autologous blood can produce PRP with concentration of platelets of at least 1 × 10 6 cell/ µ L that is almost 5 times higher than the platelet concentration in the whole blood [ 45 ]. Platelets from majority of our patients, especially those who have diabetes, were easier to aggregate after second centrifugation as we observed in laboratory, which may reflect their behavior in blood circulation [ 46 ]. Aggregated platelet releases various cytokines and growth factors that in turn activate endothelium [ 47 ].…”
Section: Discussionmentioning
confidence: 85%
“…Marx reported that double centrifugation of autologous blood can produce PRP with concentration of platelets of at least 1 × 10 6 cell/ µ L that is almost 5 times higher than the platelet concentration in the whole blood [ 45 ]. Platelets from majority of our patients, especially those who have diabetes, were easier to aggregate after second centrifugation as we observed in laboratory, which may reflect their behavior in blood circulation [ 46 ]. Aggregated platelet releases various cytokines and growth factors that in turn activate endothelium [ 47 ].…”
Section: Discussionmentioning
confidence: 85%
“…However, as compared with nondiabetic controls, angiogenic activities of platelets remain unaltered in T2D patients (Miao, Zhang, Huang, & Li, 2016). Some authors have also found that PRP from diabetic patients releases more VEGF and increases proliferation and migration of endothelial cells at larger extent, compared with PRP from healthy donors (Etulain et al, 2018; Karina et al, 2019). Notably, solid evidence supports the use of autologous PRP for the treatment of diabetic foot ulcers (Hirase, Ruff, Surani, & Ratnani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, VEGF in PRP mainly takes part in angiogenesis. 31 EGF is a mitogenic and chemotactic factor for fibroblasts and epithelial cells. 32 PDGF is also a mitogenic and chemotactic protein for fibroblasts and endothelial progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through launching signalling cascades, these growth factors will initiate multiple cellular biochemical changes. For example, VEGF in PRP mainly takes part in angiogenesis 31 . EGF is a mitogenic and chemotactic factor for fibroblasts and epithelial cells 32 .…”
Section: Discussionmentioning
confidence: 99%